Demonstrasi Eco Enzyme melalui Media Sosial dan Modul dalam Pemanfaatan Sampah Organik di Desa Kuok - Burhanuddin Burhanuddin; Syafira Aulia Rangganis; Aisyah Hilal; Rizno Fadhil; Tiyara Fany Mansyah; Sofia Yohana Simanjuntak; Ivo Ayu Nur Fadhilla; Hilda Mutiara; Zilzha Sari Maulana (Institut Pertanian Bogor, 2023)
Kuok is one of the villages in Kampar Regency that has yet to utilize its household waste, both organic and inorganic waste. This activity aims to educate on processing and utilizing household organic waste into a multi-purpose eco-enzyme solution through social media demonstrations and modules in Kuok Village. The method of this activity is based on the YouTube channel of KKN-T IPB June-August 2021 Kamparkab02. The target training participants are the community, community organizations and leaders of Kuok Village, 100 participants with cell phone devices and YouTube, Instagram and WhatsApp applications. The theory part of the video is 12 minutes long, and the practical part of making eco enzymes is 3 minutes long. During seven days, there were 158 views out of the target of 100 views, with 23 likes out of the target of 50 likes, and the number of comments was 15 out of 30 comments. As many as 50% of the viewers are homemakers, 10% are village officials, and the rest are youth from Kuok Village. As many as 62.5% of people stated that the eco enzyme processing video was more effective than the module. Both the video and the module have positively impacted knowledge, attitudes and actions and have enabled people to process their organic waste into eco enzymes.